Development of Five-Step Diagnostic Test on Light Wave Concepts to Analyze Students’ Understanding Map on The Concepts - Ismi R. Setiaji; Frida U. Ermawati (Radiasi : Jurnal Berkala Pendidikan Fisika, 2022)
During the Physics learning processes, students often have difficulty in understanding the concepts so that misconceptions occur. This is what was found in the Light Wave concepts when the Authors did the pre-research at one high school in Nganjuk. For example in Light Diffraction, students assumed that light diffraction be able to bending when it passes through all slit size, does not produce interference, and new waves. The truth is, diffraction in Light Wave occurs when light bends through a small slit and is characterized by interference and a new wave pattern. The misconceptions that occur in the Light Wave have the potential to hinder students' understanding of the following concepts, so they must be detected immediately. This article intends to report the results of writing the five-step conception diagnostic test on the Light Wave concepts, examine its feasibility, and then use it to map students' understanding concepts, as well as to identify the most dominant internal factors that lead students' misconceptions. Based on the feasibility test results, ten valid and reliable questions were selected so they can be used to test students' conceptions. The details are: the internal validity 96% (very valid), the external content validity consists of Correct Fake and Incorrect Fake scores are 3.3% and 4.5% (<10%) respectively, the construct external validity (rxy)=0.416>rtable=0.2638, and the reliability (r11)=0.796 (very reliable). Of the 19 students that were mapped using this feasible diagnostic test, 61.05% of them experienced a lack of knowledge.